Dynamic Interfacial Printing for Monodisperse Droplets and Polymeric Microparticles. Issue 1 (15th March 2016) - Liao, Shenglong; He, Yonglin; Wang, Dingguan; Dong, Libing; Du, Wenbin; Wang, Yapei
Abstract : A dynamic interfacial printing technique (DIP) is developed for preparing monodisperse droplets and polymer particles with high degree of uniformity. The DIP system is cost effective and it can be set up in a few minutes. The printing pipeline endures almost all the organic solvents, offering great promise for exploiting functional droplets or particles with long‐term service.